Ethnic aspects of settlement in Ius Valachicum in medieval Poland (from the 14th to the beginning of the 16th century - Jawor, Grzegorz (Balcanica Posnaniensia. Acta et studia, 2015)
The purpose of this article is to present the relationships which occurred between the settlement of numerous villages on the Wallachian law in the mountainous regions of Medieval Poland and the influx of settlers representing the Wallachian ethnos in this area. Without doubt, both Poles and Ruthenians could not play a decisive role in this process for they did not have the essential skills related to the economic exploitation of mountains, and they were particularly not able to conduct a pastoral economy on a mass scale. They were also not able to independently adapt the forms of social organisation of villages, which were specific for the Wallachian law. The Vlachs, pouring into the studied area throughout the 14th to 16th centuries, were arguably not numerous, but they played a key role in organising new settlements in the mountains. A particularly significant role in this process was played by the chiefs of the Wallachian villages-knyazes (knezes). They had adequate knowledge, financial possibilities as well as administrative and judicial power over the rest of the people in order to become a group, which, on the one hand, was disseminating the Wallachian law, and on the other hand, was consequently standing up for the Wallachian law which was beneficial to them. Even though they relatively quickly underwent assimilation processes and integration with the local surroundings, losing their original ethnic distinctiveness, the Wallachian law was still being spread. In that way, it turned from being an ethnic law into a symbol of privileging all people who were using it, regardless of their ethnicity.